Long in the tooth: evolution of sabertooth cat cranial shape. Issue 3 (8th April 2008) - Slater, Graham J.; Van Valkenburgh, Blaire
Abstract : Sabertooths exhibit one of the most extreme feeding adaptations seen in mammals. The functional consequences of accommodating extremely elongate upper canine teeth are severe, resulting in a well-documented suite of cranial modifications. We used geometric morphometric methods to study the evolution of overall shape in the skulls of extant and extinct feline and machairodontine felids, as well as extinct nimravids. Trends in skull evolution were evaluated by using relative warps analysis and tested for association with body size and canine tooth length. Primitive sabertooths from all lineages exhibit cranial shapes more similar to conical-toothed cats, despite the presence of moderately developed saberteeth. More-derived forms in both nimravids and felids diverge in skull morphospace to form two distinct sabertooth types (dirk-toothed and scimitar-toothed) that differ in canine shape. Skull shape in conical-toothed cats is strongly associated with body size, but not canine length. However, within each sabertooth lineage, skull shape is significantly correlated with canine length, suggesting that gape-related demands drove the evolution of sabertooth skull morphology.